Evaluation of the Level of Electrolytes in Children with Steroid Sensitive or Steroid Resistant Nephrotic Syndrome - Alwan, Ahmed H.; Al-Shammaa, Nawal M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Childhood idiopathic nephrotic syndrome is one of the most common conditions pediatric nephrologists encounter globally. Nephrotic syndrome is characterized by proteinuria, hyperlipidemia, and edema. The degree and duration of proteinuria have an impact on serum electrolyte levels. However, local data is limited.Objectives: To assess and compare the degree of electrolyte imbalance and its relationship to kidney function indicators during relapse and remission in children with idiopathic nephrotic syndrome.Methods: In this case-control study, blood samples were collected from 80 Iraqi children with an age range of (2-14) years. They were divided into three groups: Group I (20 individuals with steroid-sensitive nephrotic syndrome (SSNS)), Group II (20 individuals with steroid-resistant nephrotic syndrome (SRSN)), and Group III (40 healthy individuals as the control group). Serum electrolyte levels (Na, Ca, Cl, and K) were measured by an ion-selective electrode (9180 electrolyte analyzer). Blood creatinine and urea were measured by a Cobas c311 autoanalyzer during the relapse and remission phase. The patients were clients of the pediatric nephrology consultation center at the Children's Teaching Hospital / Baghdad Medical City and Al-Batoul Teaching Hospital for Women and Children from 15 February to 20 August 2022. The controls were healthy children whose medical history was reviewed to eliminate a history of kidney disease and underwent a comprehensive physical examination. Controls were recruited from a network of family, friends, relatives, and the National Autism Center/ Child Protection Teaching Hospital affiliated with Medical City/Baghdad.Results: Serum Calcium levels showed a clear decrease in all SSNS and SRSN patients compared to the control group. The levels of Sodium and Chloride were significantly lower than the control group during the relapse phase. The results of the relapse phase of SRNS patients indicated higher serum potassium concentration compared with the control group and the SSNS patient group, with a statistically significant difference).Conclusion: All children with idiopathic nephrotic syndrome had hypocalcemia in the relapse and remission phase. SRNS cases had hyperkalemia, Sodium, and chloride fluctuated between low levels during the relapse phase and normal levels during the remission phase.